Autoimmune polyuria – polydipsia syndrome in the postpartum period in a 27-year-old woman - Paz-Ibarra, José Luis (2021)
Autoimmune hypophysitis is a condition characterized by lymphocytic infiltration of the pituitary resulting in deficiency of one or more hormones of both the adenohypophysis and the neurohypophysis. For diagnosis, a high index of suspicion is necessary, even more so considering the temporal relationship with pregnancy or childbirth. Clinical and imaging features are suggestive of the diagnosis. Although the definitive diagnosis is by biopsy, this is not usually performed because of the potential adverse effects of the procedure. We present a case describing the form of manifesting features on magnetic resonance imaging.